Recent topics on gastrointestinal allergic disorders - Yoshiyuki Yamada (The Korean Pediatric Society, 2023)
Gastrointestinal (GI) allergies are broadly associated with food allergies and divided into groups based on the degree of allergen-specific immunoglobulin E (IgE) involvement: IgE-mediated, non-IgE-mediated, and mixed. Non-IgE-mediated GI food allergies are mostly observed in neonates and infants and include food protein-induced enterocolitis syndrome (FPIES), food protein-induced allergic proctocolitis (FPIAP), and food protein-induced enteropathy (FPE). In addition to the classical phenotype, unique phenotypes such as vomiting and bloody stool, suspected sepsis, and overlapping eosinophilic GI disorders (EGIDs) have increased in Japan over the past 2 decades. Some of these cases were defined as having chronic FPIES. More recently, cases of hen's-egg FPIES in Japan have increased dramatically since 2018, albeit for unknown reasons. Typical mixed-type food allergies are EGIDs, characterized by prominent eosinophil infiltration in the GI tract leading to GI symptoms. EGIDs are broadly classified into eosinophilic esophagitis (EoE) and non-EoE EGIDs that involve the GI tract with the exception of the esophagus. Of the EGIDs, EoE is the best known, as the number of cases has increased dramatically in Western countries, whereas pediatric EoE remains rare in Asia and non-EoE EGIDs may be more prevalent in Japan. A recent Japanese national survey showed that pediatric non-EoE EGIDs were persistent and severe compared to those in adults, possibly requiring further effective therapeutic options. Among the EGIDs, FPIAP is pathologically diagnosed as an infantile form of eosinophilic colitis. In addition, recent FPIES and FPE cases also involved eosinophilic inflammation. Recent cases of GI allergies may be associated with type 2 inflammation. A better understanding of the interactions between GI allergies and type 2 inflammation may clarify the pathogenesis of the recent increase in GI allergies.